Oncological Outcomes of Robotic-Assisted Surgery With High Dissection and Selective Ligation Technique for Sigmoid Colon and Rectal Cancer - Yin, Tzu-Chieh; Su, Wei-Chih; Chen, Po-Jung; Chang, Tsung-Kun; Chen, Yen-Cheng; Li, Ching-Chun; Hsieh, Yi-Chien; Tsai, Hsiang-Lin; Huang, Ching-Wen; Wang, Jaw-Yuan (Frontiers in Oncology, 2020)
Background Curative resection of sigmoid colon and rectal cancer includes “high tie” of the inferior mesenteric artery (IMA). However, IMA ligation compromises blood flow to the anastomosis, which may increase the complication rate. We present preliminary experiences of operative and oncologic outcomes of patients with rectal or sigmoid colon cancer who underwent robotic surgery employing the high dissection and selective ligation technique. Methods Over May 2013 to April 2017, 113 stage I–III rectal or sigmoid colon cancer patients underwent robotic surgery with the single-docking technique at one institution. We performed D3 lymph node dissection and low-tie ligation of the IMA (i.e., high dissection and selective ligation technique). Clinicopathological features, perioperative parameters, and postoperative outcomes were retrospectively analyzed. Overall survival (OS) and disease-free survival (DFS) were calculated using the Kaplan–Meier method. Results Sphincter preservation rate was 96.3% in rectal cancer patients. Median number of harvested lymph nodes was 10 with and 17 without preoperative concurrent chemoradiotherapy, respectively. Apical nodes were pathologically harvested in 84 (82.4%) patients. R0 resection was performed in 108 (95.6%) patients. Overall complication rate was 17.7%; but most complications were mild and the patients recovered uneventfully. Estimated 5-year OS was 85.6% and 3-year DFS was 79.6% after median follow-up periods of 47.1 months (range, 5.3–83.3). Conclusions High dissection of the IMA and selective ligation of the major feeding vessel to the sigmoid colon or rectum can be safely performed using da Vinci Surgical System, yielding favorable clinical and oncologic outcomes in rectal or sigmoid colon cancer treatment.